Delivery of tacrolimus with cationic lipid-assisted nanoparticles for ulcerative colitis therapy. (31st May 2018) - Wang, Ji-Long; Gan, Yun-Jiu; Iqbal, Shoaib; Jiang, Wei; Yuan, You-Yong; Wang, Jun
Abstract : FK506-loaded cationic-assisted nanoparticles (CLANs) accumulate in the colon and enhance the therapy of DSS-induced colitis. Abstract : Oral drug delivery with nanoparticles has demonstrated great potential for drugs with poor bioavailability. Efficient delivery is possible by overcoming both the mucus and epithelial barrier of the gastrointestinal tract (GIT). Cationic lipid-assisted nanoparticles (CLANs), which are composed of amphiphilic block copolymers and cationic lipids, have been well studied and have been proved beneficial for drug delivery. In this study, CLANs prepared by poly(ethylene glycol)- block -poly(lactic acid) (PEG- b -PLA) and 1, 2-dioleoyl-3-trimethylammonium-propanechloride (DOTAP) or N, N -bis(2-hydroxyethyl)- N -methyl- N -(2-cholesteryloxycarbonyl aminoethyl)ammoniumbromide (BHEM-Chol) were used for oral delivery of tacrolimus (FK506) for ulcerative colitis treatment. The average size of these nanoparticles is around 110 nm and the zeta-potential is 35 mV. These nanoparticles maintained their size in buffer solutions of pH 1.2 and 6.8, and slowly release the encapsulated drug. CLANs can be accumulated in the colon and transported through the epithelium in the colitis model by dextran sulfate sodium salt (DSS), leading to attenuation of DSS-induced colitis.